Personalising public services : Understanding the personalisation narrative. - Needham, Catherine (Policy Press, 2011)
This book focuses on how personalisation - the idea that public services should be tailored to the individual, with budgets devolved to the service user or frontline staff - evolved as a policy narrative and has mobilised wide-ranging political support.